Efektifitas Pelaksanaan Senam Kaki Diabetic dalam Menurunkan Intensitas Nyeri pada Pasien Diabetus Mellitus di Rumah Sakit Siti Khodijah Sepanjang - Eni Sumarliyah; Suyatno Hadi Saputro (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
The incidence of diabetes mellitus is increasing which causes pain in the legs of sufferers. Safety and comfort needs will not be fulfilled if the patient experiences pain, therefore nurses as professional health workers who in their main task are to meet the basic needs of patients, must be able to understand the response and behave professionally in dealing with pain problems that occur inpatient. One effort to reduce pain intensity is by implementing diabetic foot exercises in patients with diabetes mellitus. The purpose of this implementation is to find out the effectiveness of the implementation of diabetic foot exercises in reducing pain intensity in patients with diabetes mellitus in the sacred hospital throughout. The design of this study is the study of experimental design of Static Group Comparison. The population is patients who are hospitalized in Siti Khodijah. Along with the technique of simple random sampling. Data collection through questionnaires and observations, then the data is processed using and analyzed by Spearman Rho analysis and then concluded. Based on the results of the study, it was found that before the leg exercises most respondents experienced moderate pain, namely 19 people (63%), after doing leg exercises most of the respondents experienced mild pain, 21 people (70%) experienced mild pain. While the results of statistical tests show that the provision of foot exercises is effective in reducing pain intensity in patients with Diabetes Mellitus with the results of ρ = 0.000.